The consequences of ignoring the precedent of the Inter-American Court in the system of sources of Colombian law: A reflexive approach on the role that the judge and the lawyer must assist (Encuentros, 2023)
The precedent as a direct source of law is a relatively new topic in systems that have been built under the conceptual bases of what was called, as the continental or Roman-Germanic system, which marked the vision and tradition of legal-normative systems such as the Colombian, where the precedent still seems to have many aspects to evolve to achieve, When this happens, it will be necessary to conceive in the same sense the precedent of the Inter-American Court, which has the same binding force as our traditional sources, will be the conjunction of all these criteria, which will provide the basis for understanding the scope of constitutional and conventional recognitions in our environment.
Keywords: Precedent; convention; constitution; source; binding nature; evolution